Kontribusi Asuransi Jiwa terhadap Pertumbuhan Ekonomi dan Stabilitas Finansial di Indonesia - Eka Tripustikasari (Journal of New Trends in Sciences, 2025)
This study aims to analyze the contribution of the life insurance sector to economic growth and financial system stability in Indonesia during the period from 2013 to 2022. Using a quantitative approach and linear regression method, the study finds a positive and statistically significant relationship between life insurance premiums and real Gross Domestic Product (GDP) growth. Additionally, the life insurance sector acts as a long-term funding provider that supports financial market stability through investments in financial instruments such as government bonds. These findings indicate that the life insurance industry not only offers financial protection for individuals but also serves as a key pillar of economic development and financial system resilience. The study recommends enhancing insurance inclusion, financial literacy, and strengthening regulation and corporate governance in life insurance companies to fully leverage their potential contribution to Indonesia’s economy